A preliminary phylogenetic analyses of schismatoglottis calyptrata complex utilizing nuclear ITS region - Nurul Fatini Shahirah, binti Suharizan (Faculty of Resource Science and Technology, 2012)
Sehismatoglottis ealyptrata complex (Schismatoglottideae: Araceae) consist of at least 40 species. This study focused on six accessions of Sehismatoglottis calyptrata complex from Kuching, Sibu and Selangor. Molecular investigation was carried out to resolve the relationship between the species investigated. The nuclear ITS region located in nuclear ribosomal DNA (nrDNA) were used for this study. DNA was extracted from dried leaf using CTAB method. Extracted DNA were amplified and purified before sending for sequencing at a commercial company. The sequences obtained were checked manually and aligned in BioEdit ver 7.0.5 together with an outgroup, Phi/onotion americanum. Phylogeny analyses were carried out in PAUP ver v.4.0b10 for maximum parsimony and RAxML for maximum likelihood. Maximum parsimony and maximum likelihood analyses showed strong and moderate bootstrap support (MP: 100%, ML: 43%) for the ingroups excluding Schismatoglottis calyptrata AR 3586. This study shows that all the species sampled from Sarawak are closely related based on the molecular evidence.